Mesolithic Scandinavian foraging patterns and hunting grounds targeted through laser ablation derived 87Sr/86Sr ratios at the Early-Mid Holocene site of Huseby Klev on the west coast of Sweden. (1st October 2022) - Boethius, Adam; Kielman-Schmitt, Melanie; Robson, Harry K.
Abstract: Mobility is one of the most fundamental aspects of a foraging society. Since prehistoric mobility is often difficult to identify in the archaeological record, our understanding is largely based on comparison with ethnographic communities. In recent years the application of 87 Sr/ 86 Sr isotope analysis has, however, greatly broadened our knowledge of mobility in the past. Despite this, few studies have been undertaken on faunal remains to explore their mobility patterns and infer human exploitation patterns with more precision. In this contribution we sampled 28 mammal teeth from three different occupation phases at the Early to Mid-Holocene coastal site of Huseby Klev, Sweden. We first established the local baseline for seven geographical areas in the region surrounding Huseby Klev. Then, by applying laser ablation-multi collector-inductively coupled plasma-mass spectrometry to the selected teeth, we identified the likely origins of a range of terrestrial and marine fauna, and the possible human mobility patterns required in their exploitation. Overall, our results demonstrate that the prehistoric communities inhabiting Huseby Klev undertook both short- and long-distance forays for the exploitation of particular species. By relating inferences on hunting grounds, derived from strontium isotope data, to zooarchaeological evidence from the site and ethnographic human mobility patterns, we establish and discuss the prerequisites for landscape utilization. Lastly, we demonstrate that glacial meltwater may have temporally affected the local oceanic Sr ratios – suggesting significantly increased soil and bedrock weathering may influence the Sr values in aquatic ecosystems and, consequently, should be considered in such regions and at times of melting glaciers. By applying the method to additional sites and assemblages in the future, our understanding of prehistoric mobility will be greatly enhanced. Highlights: Strontium isotope ratios were analysed for mammals from an Early Holocene coastal site from Sweden. Mammal mobility and origin were ascertained using laser ablation technology. Results suggest hunting grounds, territories and human foraging ranges are traceable. The method enables studies of mobility and land use related to prehistoric foraging societies.